The Concept of Space and Extension in Leibniz's Philosophy - Michalski, Rafał Andrzej (Ruch Filozoficzny, 2025)
This article examines Leibniz's conception of space and extension, emphasizing their ideal nature and integration with his dynamic theory of matter. Space, extension, and secondary matter are interpreted as phenomenal manifestations of monadic activity—non-extended, simple metaphysical substances that structure phenomena through their internal active and passive forces. Space is characterized as an ideal relational order that facilitates the phenomenal appearance of material bodies as aggregates of monads. The extension of secondary matter, in turn, represents how these relational structures are made accessible to sensory perception.